Modeling the strain localization around an underground gallery with a hydro-mechanical double scale model; effect of anisotropy. (May 2017) - van den Eijnden, A.P.; Bésuelle, P.; Collin, F.; Chambon, R.; Desrues, J.
Abstract: This paper concerns the application of a finite element squared approach for modelling hydromechanical coupling in the simulation of gallery excavation in the context of radioactive waste repositories. The micromechanics of Callovo-Oxfordian claystone is modelled at the microscale, taking into account the interaction of different mechanical constituents and its interaction with pore fluid. In a framework of computational homogenization, the micromechanical behaviour is coupled to the macroscale boundary value problem of a poromechanical continuum with local second gradient paradigm. The simulations concern several cases of the "Transverse action" benchmark by Andra, in the context of which the model is used.